The innovation of cotton fiber from recycled cloth as coloring agent for polypropylene via injection moulding - Main, Nor Mazlana; Othman, Mohd Hilmi; Tiang, Ming Yuan; Marsi, Noraini (Penerbit UTHM, 2020)
Plastics can be coloured in many different ways. In the present application, the colouring agent that is used in the plastic industries are the dyes and pigments. Both methods are sustantially different and produce specific results. Dyes are defined as colourants that are (completely) soluble in a polymer at the processing temperature. Pigments are organic or inorganic solid particles that are insoluble in polymers...